Regulation of the Interfaces Between Argyrodite Solid Electrolytes and Lithium Metal Anode - Pang, Bo; Gan, Yongping; Xia, Yang; Huang, Hui; He, Xinping; Zhang, Wenkui (Frontiers in Chemistry, 2022)
Lithium-ion batteries (LIBs) are widely used in portable electronic devices, electric vehicles and large scale energy storage, due to their considerable energy density, low cost and long cycle life. However, traditional liquid batteries suffer from safety problems such as leakage, thermal runaway and even explosion. Part of the issues are caused by lithium dendrites puncturing the liquid electrolyte during cycling. In order to achieve the objective of higher safety and energy density, a rigid solid-state electrolyte (SSE) is proposed instead of liquid electrolyte (LE). Thereinto, sulfide SSEs have received of the most attention due to their high ionic conductivity. Among all the sulfide SSEs, argyrodite SSEs are considered to be one of the most promising solid-state electrolytes due to their high ionic conductivity, high thermal stability and good processablity. On the other hand, lithium metal is an ideal material for anode because of its high specific energy, low potential and large storage capacity. However, interfacial problems between argyrodite SSEs and the anode (interfacial reactions, lithium dendrites, etc.) are considered to be important factors affecting their availability. In this mini review, we summarize the behavior, properties and problems arising at the interface between argyrodite SSEs and anode. Strategies to solve interface problems and stabilize interfaces in recent years are also discussed. Finally, a brief outlook about argyrodite SSEs is presented.